Sustainability Rumah Sakit Swasta Berbasis Transformational Leadership: Mediasi Ambidexterity dan Commitment dengan Moderasi Organizational Justice - Surastomo Budi Cahyono (Jurnal Inovasi Global, 2026)
The dynamics of the National Health Insurance policy create volatility in the health sector that demands precise synchronization between the vision of strategic leadership and the reality of organizational behavior to ensure the sustainability of hospitals comprehensively. This study constructs an integrative model to dissect the influence  of Transformational Leadership on Organizational Sustainability by involving the variables of Organizational Ambidexterity and Organizational Commitment as multiple mediators, and strategically placing Organizational Justice as a boundary condition). Using the SEM-PLS quantitative approach and the phenomenological analysis  of the Three-Box Method (scale 1-4) at a Type C Private Hospital in Bogor City, this study represents a cognitive audit of the pattern of reciprocity between leadership and staff. Inferential analysis synergized with this descriptive method is able to investigate in depth the existence of fundamental structural complexity, in which established theoretical models actively interact with the systemic inertia of the organization. There is a dichotomy between the mechanistic path and the human path that makes this study provide authoritative navigation regarding the essential role of the Golden Anchor in efforts to mitigate the negative cycle of the organization to build a stronger foundation of success. These findings provide a crucial tool for hospital leaders to understand the root causes of organizational sustainability strategies often being mired in pseudo-conditions, while providing guidance for scientifically proven strategic interventions to secure the organization's sustainable future over a very long period of time.